Social climate and hope amongst staff and prisoners in a high security male prison. Issue 1 (14th January 2021) - Gibson, Sarah
Abstract : Purpose: There is an increased focus on making prison cultures more rehabilitative, with clear evidence that certain environmental characteristics contribute towards rehabilitation. To date, limited research has explored the rehabilitative culture in a high security prison. This study aims to measure staff and prisoner ratings of social climate and their levels of hope in such an establishment. Design/methodology/approach: The research adopted a quantitative approach, using the EssenCES and State Hope Scale. Data was analysed using parametric and non-parametric tests to explore correlations/relationships between variables. Findings: Findings indicated that higher ratings of social climate were associated with higher levels of hope. Staff rated the social climate more favourably than prisoners, and Category B prisoners had higher levels of hope than Category A prisoners. No significant correlation was found between length of time in service or custody and ratings of social climate or hope. Practical implications: This paper highlights the importance of developing a positive social climate and hope, supporting the rehabilitative culture initiatives. Originality/value: This paper contributes to the limited literature on social climate and hope within UK forensic settings. Furthermore, reliability testing indicates the State Hope Scale is appropriate for use with a UK forensic population, extending its application.